Correction: Kebe, M.; Sanduleanu, M. A Low-Phase-Noise 8 GHz Linear-Band Sub-Millimeter-Wave Phase-Locked Loop in 22 nm FD-SOI CMOS. Micromachines 2023, 14, 1010 - Mamady Kebe; Mihai Sanduleanu (Micromachines)
In the published publication [...]